Velocity-selected production of 2 3S metastable positronium - Amsler, Claude; Demetrio, Andrea; Müller, Simon R.; Oberthaler, Markus K. (Physical review, 2019)
Positronium in the 23S metastable state exhibits a low electrical polarizability and a long lifetime (1140 ns), making it a promising candidate for interferometry experiments with a neutral matter-antimatter system. In the present work, 23S positronium is produced, in the absence of an electric field, via spontaneous radiative decay from the 33P level populated with a 205-nm UV laser pulse. Thanks to the short temporal length of the pulse, 1.5 ns full width at half maximum, different velocity populations of a positronium cloud emitted from a nanochanneled positron-positronium converter were selected by delaying the excitation pulse with respect to the production instant. 23S positronium atoms with velocity tuned between 7×104ms−1 and 10×104ms−1 were thus produced. Depending on the selected velocity, a 23S production efficiency ranging from ∼0.8% to ∼1.7%, with respect to the total amount of emitted positronium, was obtained. The observed results give a branching ratio for the 33P−23S spontaneous decay of (9.7±2.7)%. The present velocity selection technique could allow one to produce an almost monochromatic beam of ∼1×10323S atoms with a velocity spread of <104ms−1 and an angular divergence of ∼50 mrad.
Die Zahl "3" im Titel ist hochgestellt
Gesehen am 29.05.2019